2008
DOI: 10.1186/1475-2875-7-32
|View full text |Cite
|
Sign up to set email alerts
|

Costs and effects of the Tanzanian national voucher scheme for insecticide-treated nets

Abstract: Background: The cost-effectiveness of insecticide-treated nets (ITNs) in reducing morbidity and mortality is well established. International focus has now moved on to how best to scale up coverage and what financing mechanisms might be used to achieve this. The approach in Tanzania has been to deliver a targeted subsidy for those most vulnerable to the effects of malaria while at the same time providing support to the development of the commercial ITN distribution system. In October 2004, with funds from the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 13 publications
3
87
0
Order By: Relevance
“…45,49,50 In the fourth study, the delivery of partially subsidized ITNs to pregnant women via antenatal care clinics in the United Republic of Tanzania was examined. [32][33][34][35] The fifth study reviewed a stand-alone ITN campaign involving distribution of fully subsidized nets to children under 5 in the Micheweni district of Zanzibar. 41 Table 2 shows the variety of study designs used to assess ITN delivery strategies.…”
Section: Systematic Reviewsmentioning
confidence: 99%
See 3 more Smart Citations
“…45,49,50 In the fourth study, the delivery of partially subsidized ITNs to pregnant women via antenatal care clinics in the United Republic of Tanzania was examined. [32][33][34][35] The fifth study reviewed a stand-alone ITN campaign involving distribution of fully subsidized nets to children under 5 in the Micheweni district of Zanzibar. 41 Table 2 shows the variety of study designs used to assess ITN delivery strategies.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…22,27 The study at the national scale reported an economic cost of US$ 10.77 per ITN delivered. 25,35 Of the four studies that evaluated the delivery cost of partially subsidized ITNs, three investigated delivery through the retail sector and one investigated voucher use. Studies of retail-based delivery reported financial costs of US$ 5.47 and US$ 11.16 per ITN delivered in Burkina Faso and Malawi, respectively, and of US$ 12.57 and US$ 18.72 per treated-net-year in the United Republic of Tanzania and Malawi, respectively.…”
Section: Costsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this is not perceived as appropriate to the whole population. Lastly, insecticide treated bed nets (ITNs) is an option, which have shown to be an effective, feasible and economic attractive measure in reducing mortality and morbidity from malaria (Goodman and others 2001, Hanson and others 2003, Lengeler 2004, Mueller 2008and Mulligan 2008.…”
Section: Step 4 Adaptation Optionsmentioning
confidence: 99%